IMPLEMENTASI SEM DALAM MEMBANDINGKAN PRESTASI BELAJAR SISWA SEKOLAH NEGERI DAN SEKOLAH SWASTA - -, Ernawati (Fakultas Sains dan Teknologi UIN ALauddin, 2013)
Structural Equations Modeling (SEM) is a multivariate methods applied to show simultaneous relationship between indicator variables observed directly with latent variables which cannot be observed directly. SEM is a method combining technique or ideas of regression analysis, path analysis, and confirmatory factor analysis. This research axaminies the application of SEM in education that involve continous variables and ordinal variables/category , in this study applied to the two groups in the form of a group of state school students and groups of students from private schools. From the results obtained that socioeconomic factors have a positive impact on student achievement both group 1 and group 2, But this effect is relatively higher in students from state schools compared to students from private schools.Key words: SEM, Varian Covariance Matrices.